Anti‐viral therapy for prevention of perinatal HBV transmission: extending therapy beyond birth does not protect against post‐partum flare. Issue 10 (25th March 2014) - Nguyen, V.; Tan, P. K.; Greenup, A.‐J.; Glass, A.; Davison, S.; Samarasinghe, D.; Holdaway, S.; Strasser, S. I.; Chatterjee, U.; Jackson, K.; Locarnini, S. A.; Levy, M. T.
Summary Background Antepartum anti‐viral therapy (AVT) is often administered to prevent perinatal transmission of hepatitis B virus (HBV) infection. Little is known about the effect of AVT on post‐partum flare rates and severity. Aim To examine whether extending AVT beyond birth influences the post‐partum course. Methods One hundred and one pregnancies in 91 women with HBV DNA levels ≥log 7 IU/mL were included. AVT (initially lamivudine, later tenofovir disoproxil fumarate) was commenced from 32 weeks gestation and stopped soon after birth and at 12 weeks post‐partum. Outcomes according to post‐partum treatment duration were examined: Group 1 = AVT ≤4 weeks (n = 44), Group 2 = AVT >4 weeks (n = 43), Group 3 = no AVT (n = 14). Results The majority of women were HBeAg+ (97%), median age 29 years, baseline HBV DNA log 8.0 IU/mL and follow‐up 48 weeks post‐partum. Post‐partum treatment duration was 2 weeks for Group 1 and 12 weeks for Group 2, P < 0.01. Flare rates were not significantly different: Group 1 = 22/44 (50%), Group 2 = 17/43 (40%) and Group 3 = 4/14 (29%), P = 0.32. Onset of flare was similar at 8/10/9 weeks post‐partum for Groups 1/2/3 respectively, P = 0.34. The majority of flares spontaneously resolved. HBeAg seroconversion (n = 1/5/1 in Groups 1/2/3, P = 0.27) was not associated with treatment duration or the occurrence of a post‐partum flare. Conclusions Post‐partum flares are common and usually arise early after delivery. They are often mild in severity and most spontaneously resolve. Extending anti‐viral therapy does not protect against post‐partum flares or affect HBeAg seroconversion rates.